Investigating the phenotypic and genetic associations between personality traits and suicidal behavior across major mental health diagnoses: short communication - Kálmán, János L.; Yoshida, Tomoya; Andlauer, Till F. M.; Schulte, Eva C.; Adorjan, Kristina; Alda, Martin; Ardau, Raffaela; Aubry, Jean-Michel; Brosch, Katharina; Budde, Monika; Chillotti, Caterina; Czerski, Piotr M.; et al. (European archives of psychiatry and clinical neuroscience, 2022)
Personality traits influence risk for suicidal behavior. We examined phenotype- and genotype-level associations between the Big Five personality traits and suicidal ideation and attempt in major depressive, bipolar and schizoaffective disorder, and schizophrenia patients (N = 3012) using fixed- and random-effects inverse variance-weighted meta-analyses. Suicidal ideations were more likely to be reported by patients with higher neuroticism and lower extraversion phenotypic scores, but showed no significant association with polygenic load for these personality traits. Our findings provide new insights into the association between personality and suicidal behavior across mental illnesses and suggest that the genetic component of personality traits is unlikely to have strong causal effects on suicidal behavior.